If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 + -3x = 36 Reorder the terms: 4 + 9x + -3x = 36 Combine like terms: 9x + -3x = 6x 4 + 6x = 36 Solving 4 + 6x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 36 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 36 + -4 6x = 36 + -4 Combine like terms: 36 + -4 = 32 6x = 32 Divide each side by '6'. x = 5.333333333 Simplifying x = 5.333333333
| 3x+5+4x-12=15x-27 | | -2x+10=12-3x | | 1-4(u-1)=0 | | 4y-4/8+26/2=1/4 | | 2x^3+4x^2-3x=0 | | 2+9p-3p=14 | | 8+((12+5)*4)/2 | | 4/3+y/2=5/2 | | 2x^4+x^3-21x^2=0 | | x^2y=x^2-3y-1 | | 2x+5(x+9)=129 | | 3d+(9-2d)=51 | | 4t+1/4=t+5/8+t-3/8 | | 4x+18=180 | | 9x^2-12=13 | | 6+2j-4=4 | | -n-(3+9n)=-10-14n | | t+.02t=612 | | 4a+0.2=50 | | 2.9y-4.6=0.6y | | 7z-6z=18+4 | | 2x-3(4x+5)-10=10x+3-4 | | (x-3)(x+3)=2x^2+3x+29 | | 23/6x5/6+23/6x13/6 | | -1/3+2t=-1/3(9t-2) | | D=tres | | y^2-100=4y | | 10y-4y-8=20 | | (u-4)^2/3 | | 4k=60+6k | | 9/5(k-273.15) | | 3-2/6b=1/3b-7 |